2019
DOI: 10.12720/sgce.8.5.505-516
|View full text |Cite
|
Sign up to set email alerts
|

A new concept to improve the lithium plating detection sensitivity in lithium-ion batteries

Abstract: Lithium plating significantly reduces the lifetime of lithium-ion batteries and may even pose a safety risk in the form of an internal short circuit, leading to catastrophic cell failure. Low temperatures, high charge currents and battery age are known to be contributing factors to increased lithium plating. To reduce or avoid battery ageing induced by lithium plating, a method for lithium plating detection is essential to help understand the favourable conditions under which battery charging is optimised. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The results show that reversible lithium plating was only found in the first two fast charge cycles. This reaffirms the findings from [30] and the literature contained within [3,22] that higher levels of plating lead to increased levels of capacity reduction and therefore must be avoided to prolong battery life.…”
Section: Capacity Fade Analysissupporting
confidence: 82%
See 4 more Smart Citations
“…The results show that reversible lithium plating was only found in the first two fast charge cycles. This reaffirms the findings from [30] and the literature contained within [3,22] that higher levels of plating lead to increased levels of capacity reduction and therefore must be avoided to prolong battery life.…”
Section: Capacity Fade Analysissupporting
confidence: 82%
“…To avoid lithium plating and to improve charge time, charge current in the third stage must be appropriately selected. From [30], for this cell, it was found that lithium plating was not detected with charge rates lower than 0.25C at ambient temperatures above 5 o C and reversible plating detection ability was maximum with a cut-off charge rate of 0.25C. As discussed in [30], lithium stripping begins in the…”
Section: Proposed Charging Control Strategiesmentioning
confidence: 82%
See 3 more Smart Citations